Genetic database software as medical devices. Issue 11 (11th October 2018) - Thorogood, Adrian; Touré, Seydina B.; Ordish, Johan; Hall, Alison; Knoppers, Bartha
Abstract: This article provides a primer on medical device regulations in the United States, Europe, and Canada. Software tools are being developed and shared globally to enhance the accessibility and usefulness of genomic databases. Interactive software tools, such as email or mobile alert systems providing variant classification updates, are opportunities to democratize access to genomic data beyond laboratories and clinicians. Uncertainty over the reliability of outputs, however, raises concerns about potential harms to patients, especially where software is accessible to lay users. Developers may also need to contend with unfamiliar medical device regulations. The application of regulatory controls to genomic software could improve patient and user safety, but could also stifle innovation. Legal uncertainty for developers is compounded where software applications are made available globally (implicating multiple regulatory frameworks), and directly to lay users. Moreover, there is considerable uncertainty over the application of (evolving) medical device regulations in the context of both software and genetics. In this article, criteria and examples are provided to inform determinations of software as medical devices, as well as risk classification. We conclude with strategies for using genomic communication and interpretation software to maximize the availability and usefulness of genetic information, while mitigating the risk of harm to users. Abstract : This article provides a primer on medical device regulation of software that interprets and exchanges genomic data. We compare tests for determining if software qualifies as a medical device across the United States, Europe, and Canada, as well as risk classifications and regulatory controls. Medical device regulation of both software and genetic tools remains uncertain, raising competing concerns: insufficient regulation allows low quality outputs to undermine patient care, while excessive regulation stifles development of innovative tools delivering precision medicine.